Research of the Transmission Error of Planetary Transmission System for Hub Motor - Chen Haoran; Qin Xunpeng; Zhang Jiang (Jixie chuandong)
Taking the planetary transmission system of hub motor as the research object,the kinematic differential equations of the system are established by considering the influence factors of time-varying mesh stiffness,meshing phase and equivalent mesh error,and the Runge-Kutta method is used to get the system transmission error. Based on the transmission error curve,the influence of various error and support stiffness on the system transmission error amplitude is analyzed,and the initial phase of the error is optimized. The results show that the magnitude of the error value is proportional to the amplitude of the system transmission error,the change of the initial phase of the error could reduce the transmission error amplitude without changing the component accuracy,the magnitude of the support stiffness is inversely proportional to the amplitude of the system transmission error. The research work has provided guidance for the design of the planetary transmission system,which reduces the manufacturing difficulty and the installation cost.